The Influence of Social Status, Economic Status, Political Affiliation of Parents, and Organizational Experience on the Empty Box Phenomenon in the 2024 Maros Regional Head Election - Yusa’ Farchan; Inrinofita Sari; Asriadi (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study analyzes the influence of Social Status, Economic Status, Political Affiliation of Parents, and Organizational Experience on the Empty Box Discourse in the 2024 Maros Regency Regent Election. This study uses a quantitative approach with a survey method through distributing questionnaires to the public in Maros Regency to explore the relationship between variables and the empty box phenomenon in implementing regional elections. Data processing was carried out with the help of SmartPLS software using the Structural Equation Modeling Partial Least Squares (SEM-PLS) technique. The results showed that the emergence of a single candidate in the 2024 Maros regional head election was caused by the community's lack of courage to run for office, which was influenced by the strong dominance of incumbent candidates. Furthermore, people's political participation in the election is analyzed through four main variables, all of which positively affect the empty box discourse. Thus, all hypotheses in this study are accepted.